Pemanfaatan Aset Buah Pisang Lokal Menjadi Produk Jenang “Jepipet” di Desa Jampet Kecamatan Ngasem Kabupaten Bojonegoro - Abid Rohman; Aliyah; Fikri Aji Wicaksosmo (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
To increase the economic and social independence, various efforts were carried out, it includes by providing assistance to the community. This research aims to provide assistance to the community in the village of Jampet, Bojonegoro Regency, by utilizing local banana assets for making Jenang Jepipet as an original snack made from bananas from Jampet villages. The collaborative and partnership efforts built between the universities together with the Jampet villagers as a manifestation of the practice of university community engagement. By using Asset-Based Community Development (ABCD) approach, this research is a model of community assistance and empowerment to be more actively involved in utilizing all the potential and strength of assets owned by the community to create economic and social welfare. The results of this research, the community can take advantage of the opportunities and potential of their banana assets to be a product of Jenang made from banana as an icon of snacks from Jampet village.